The Role of Information Technology In Public Safety - A.KH. Yuldashev; J.T. Azimov (International Journal of Business and Quality Research, 2023)
This article discusses the importance of information technology for public safety. Threats and measures for implementing the adopted legal documents and the "road map" were also analyzed. The necessity of the public informatization process and the possibility of ensuring the economic growth of the country through it are scientifically based. In addition, the analysis of the state of affairs in the field of information protection shows that a separate concept must be introduced for the full formation of public security, and this aspect is based on our research. In addition, conclusions and recommendations regarding the expansion of the role of information technologies in public safety have been developed.